Identifying cloud forest conservation areas in Mexico from the potential distribution of 19 representative species - L. López-Arce; C. Ureta; D. Granados-Sánchez; L. Rodríguez-Esparza; A. Monterroso-Rivas (Heliyon, 2019)
Cloud forest is a sensitive and vulnerable ecosystem that is threatened by human activities as well as climate change. Previous studies have shown how transitional ecosystems such as cloud forests will be the most negatively impacted by the global increase in temperature. Therefore, the niche modeling framework was used in this study to geographically identify the areas with the climatic potential to host the largest number of key tree species in this ecosystem and to propose them as priority conservation areas. A total of 19 species were modeled using the MaxEnt algorithm; binary maps were generated for each species and combined to produce one potential suitability map and identify climatic priority areas. Thus, 7% of the national area of Mexico shows suitability for the cloud forest ecosystem, although it is currently distributed in less than 1% of the country. Finally, potential suitability areas were compared with natural protected areas, current land use and priority conservation areas. We found that of the current suitable area, only 5% coincides with some federal or state protection regime. Natural protected areas have proven to be a mechanism for forest conservation, so we must consider increasing the number and area of those protected areas that favor the conservation of these key cloud forest species.